PENGARUH INFRASTRUKTUR TELEKOMUNIKASI TERHADAP PERTUMBUHAN EKONOMI DI PROVINSI BANTEN TAHUN 2004 -2013 - Ngatono Ngatono (PROSISKO: Jurnal Pengembangan Riset dan Observasi Sistem Komputer, 2016)
Telecommunications today is one very important thing in life, communication services is perceived by society. Selullar role of communications technology in particular has a positive impact on the improvement of economic income people, this happens in Banten province as a province of the capital buffer beloved country.  In this study will be analyzed is there a significant relationship between Telecommunications infrastructure for economic growth areas in Metro Manila and also want to know how big the impact, telecommunications infrastructure represented by a mobile phone that is the number of BTS (Base transciever Station) and economic growth represented by GDP (Gross Regional Regional Income), to be able to know the purpose of this study used methods of early determination and proceed with Least Square Regression method to get the value of the amount of Telecommunications Infrastructure influence on economic pertubuhan in Banten. In the hope of this study will be made as a recommendation to the local government in order to provide the rules or policies of the telecommunications sector in order to be useful for society optimally and uniformly across the province of Banten. By sampling data from years 2004 -2013 or 10 years is found that: Telecommunications and GDP growth in Banten province showed a significant relationship, it is shown by the test results with the method of determination (R2) is equal to: 0.993. Having held testing the relationship between telecommunications infrastructure in this case represented by the BTS to GDP growth in Banten in getting a regression value of 0.134% means that it indicates that every increase of 1% BTS will contribute to the increase of GDP by 0.134%.